TANTANGAN IMPLEMENTASI PEMBIASAAN KARAKTER ISLAMI DI ERA DIGITAL: STUDI PENDAHULUAN PENGUATAN AKHLAK SISWA SEKOLAH DASAR - Apin; Euis Susi Susilawati; Okke Rosmaladewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic character education through habituation is a fundamental strategy in shaping the moral character of elementary school students. However, the rapid development of digital technology and massive gadget usage has created new challenges in implementing character habituation programs. This preliminary research aims to identify and analyze the main challenges faced by elementary schools in maintaining the effectiveness of Islamic character habituation programs amid the negative influence of the digital era. Using a systematic literature review method on 30 sources (20 national journals and 10 international journals, 2020-2026), this research identified five critical challenges: (1) low digital ethics and cyberbullying, (2) social media and gadget addiction, (3) decreased face-to-face social interaction, (4) misinformation dissemination, and (5) limited parental supervision. The analysis results show that integrating habituation management with digital literacy, school-parent collaboration, and wise technology use are strategic solutions. This research serves as an important foundation for further studies on resilient character habituation management models against digital challenges.